PERUBAHAN SOSIAL DAN MODERNISASI - A. Nurul Mutmainnah (Fakultas Ushuluddin, Adab, dan Dakwah IAIN Parepare, 2015)
Absolute social change happen anytime and anywhere. Whether the individual and the community groups if it is associated with social psychology theory of those who have the personality of innovation. Population growth will result in several individuals who have the desire autonomy and regularity. A doxa that modernization is the development goals of the third world. But look at the empirical fact that modernization can not necessarily give rise to development or overall wellbeing. Inequality could happen as in the capitalist understanding, where people work hard to raise capital, but on one side there are the citizens in terms of expertise and job availability is inadequate and materially to make the poor poorer and the rich get richer.